(3eYLe GdHdOGf aj eYQaI GdeOf hGdbQi hGdNQGH hGdYeGQ hGdSgd hGdhYQ ef cd ecGfs - (3jGbhJ Hf YHO Gddg GdQhej GdMehj, TgGH GdOjf CHh YHO Gddg,J (B626 (3g` s
(3ChdgG (B:s
(3jHJOF ef (B: (3GdChGR s
(3BNQgG (B:s
(3jfJgi Edi (B: (3GdHVjVfjI s
(3PcQ ajg CSeGA GdHdGO hGdLHGd hGdELJeGY hGdCOhjI hGdbjYGf hSGFQ eG jJYdb HQHY GdCQV GdeSchf eeG LGA NHQ ChhQO ai TYQs
(3QJHg Ydi MQha GdeYLe Edi (B28 (3HGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B178s
Keywords: (3GdLZQGajG h GdHdOGfs